An anti-internal sulfate corrosion agent and a preparation method thereof

By using anion-exchange chitosan and barium salt-doped nano CaCO3 microspheres, the internal sulfate corrosion problem caused by excessive sulfate in concrete is solved, and the effect of improving the durability of concrete and extending service life is achieved.

CN119707350BActive Publication Date: 2025-04-18SHIJIAZHUANG CHANGAN YUCAI BUILDING MATERIALS +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510214217.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-18
Estimated Expiration
2045-02-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent internal sulfate corrosion in concrete due to excessive sulfate standards, resulting in shortening of the service life of concrete structures and engineering safety issues.

Method used

An internal sulfate corrosion inhibitor is used, which consists of anion exchange chitosan, barium salt-doped nanoCaCO3 microspheres and polyacrylate/barium salt-doped nanoCaCO3 composite emulsion to slow sulfate corrosion by adsorbing sulfates, generating stable hydration products and refining concrete capillaries.

Benefits of technology

It significantly improves the durability of concrete, reduces the expansion stress and crack formation caused by sulfate corrosion, extends the service life of concrete structures, and does not reduce the strength of concrete.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an anti-internal sulfate erosion agent and a preparation method thereof, belonging to the technical field of chemical additives for building materials, and comprising the following raw materials by weight: 5-10 parts of anion exchange chitosan, 8-10 parts of barium salt-doped nano-CaCO3 microspheres, 100-120 parts of polyacrylate / barium salt-doped nano-CaCO3 composite emulsions and 1-1.5 parts of sodium polyacrylate. The anti-internal sulfate erosion agent provided by the invention has excellent resistance to sulfate erosion inside concrete caused by accelerators and sand and gravel aggregates carrying sulfate, can improve the durability of concrete, and the addition of the anti-internal sulfate erosion agent provided by the invention will not reduce the strength of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical additives for building materials, and particularly relates to an agent for resisting internal sulfate corrosion and a preparation method thereof. Background Art

[0002] Sulfate attack is a key issue affecting the durability of concrete. From the source of sulfate, sulfate attack on concrete can be divided into internal and external attack. Internal attack is caused by sulfate in the concrete components themselves. One of the main sources of sulfate in internal sulfate attack is mineral aggregates with attached sulfate or sulfate-containing minerals. In the past 30 years, internal sulfate attack caused by sulfate in aggregates has been found in tunnels and dams, causing major engineering safety problems and economic losses. The rock formations in many areas of my country contain gypsum, and some projects use gypsum-containing rocks as aggregates. In the early stages of hydration, sulfate components in concrete, such as gypsum, react with tricalcium aluminate to form calcium aluminate (AFt). At this stage, sulfate has no negative impact on concrete and can even increase the strength of concrete. However, excess gypsum remains in the hardened concrete, and gypsum will continue to dissolve SO4 2- And continue to react with the remaining tricalcium aluminate to form AFt, which causes vicious expansion and cracking. In order to prevent excessive sulfate in aggregates and cause internal sulfate erosion, GB / T14684-2011 and GB / T14685-2011 stipulate that the SO3 content in fine aggregate and coarse aggregate shall not exceed 0.5% and 1% respectively, but there is still a risk that the SO3 content is at the critical point. In addition, another major source of internal sulfate erosion is accelerator. For shotcrete, one of the most important raw materials is accelerator. The main component of alkali-free accelerator is aluminum sulfate, accounting for 15% to 40%. That is, shotcrete is affected by internal sulfate erosion at the beginning of service. In the case of high concentrations of sulfate both inside the concrete and in the environment, if effective anti-corrosion measures are not taken, bidirectional expansion can easily form through cracks, and the service life of the concrete structure will be greatly shortened. Summary of the invention

[0003] The purpose of the present invention is to provide an internal sulfate corrosion resistance agent and a preparation method thereof to solve the problems existing in the above-mentioned prior art.

[0004] One of the technical solutions provided by the present invention:

[0005] An internal sulfate corrosion resistance agent comprises the following raw materials, measured by weight: 5-10 parts of anion exchange chitosan, 8-10 parts of barium salt doped nano-CaCO3 microspheres, 100-120 parts of polyacrylate / barium salt doped nano-CaCO3 composite emulsion and 1-1.5 parts of sodium polyacrylate.

[0006] When there is an excess of sulfate in the internal components of concrete, the anion exchange chitosan component in the product of the present invention first participates in the reaction and adsorbs the sulfate in the concrete. The mechanism of chitosan adsorbing sulfate mainly involves the porous structure and nitrogen doping characteristics of chitosan, which makes chitosan have a strong adsorption capacity for sulfate, and the glutaraldehyde cross-linked chitosan with amino protection obtained after protonation modification further improves its adsorption performance for sulfate. At the same time, barium salt-doped nano-CaCO3 microspheres begin to participate in the cement hydration reaction, react with C3A in cement, and generate low-calcium hydrated calcium aluminate (3CaO·Al2O3·CaCO3·12H2O) and high-calcium hydrated calcium aluminate (3CaO·Al2O3·3 CaCO3·31H2O) that are more stable than calcium sulfaluminate. Due to the addition of nano-CaCO3, the amount of C3A that reacts with sulfate is reduced, thereby reducing the amount of calcium sulfaluminate generated, and the expansion stress in the concrete is also reduced accordingly. In addition, the generated carbon aluminate can overlap with other hydration products, making the internal structure of the concrete more compact and increasing the resistance of the external sulfate solution to enter the interior of the concrete. In the process of barium salt doped nano-CaCO3 participating in the hydration, calcium carbonate and C3A generate hydration products, which can squeeze the internal doped barium salt to the surface. Because the calcium carbonate carrier and the barium salt therein are both nanoparticles, they have a larger specific surface area, so there are more distribution points in the concrete system. If there is still excessive sulfate in the concrete system, the soluble barium salt can generate insoluble barium sulfate with it to further reduce the sulfate concentration of the concrete system, and barium sulfate can further refine the capillary pore diameter of the concrete, thereby achieving the reduction of the generation rate of gypsum and calcium sulfonate crystals, and then delaying the speed of sulfate erosion and damage of concrete. Polyacrylate / barium salt doped nano-CaCO3 composite emulsion is a slow-release component of the anti-internal sulfate erosion agent of the present invention, which can regulate the hydrolysis rate of its polyacrylate shell according to the type of acrylic ester, that is, the release rate of the barium salt doped nano-CaCO3 component, mainly for the adsorption and recovery of excessive sulfate in the quick-setting agent after the quick-setting agent is added to the sprayed concrete.

[0007] Preferably, the preparation method of the anion exchange chitosan comprises the following steps: heating the organic solvent mixture, adding the chitosan-acetic acid aqueous solution under stirring, continuing stirring to disperse the chitosan-acetic acid aqueous solution into beads, then dropping formaldehyde solution, dropping glutaraldehyde after the reaction, continuing the reaction, adjusting the pH to 7.5-8.5, heating the reaction to solidify the beads, filtering, washing with water to neutrality, extracting, filtering, washing, and vacuum drying to prepare the amino-protected glutaraldehyde cross-linked chitosan, namely the anion exchange chitosan.

[0008] More preferably, the organic solvent mixture comprises 50-60 parts of carbon tetrachloride, 50-60 parts of petroleum ether and 10-15 parts of Span-80 in parts by mass;

[0009] More preferably, the mass proportions of the chitosan-acetic acid aqueous solution, formaldehyde solution and glutaraldehyde solution are 100-120 parts, 160-180 parts and 8-10 parts respectively; the mass concentration of the formaldehyde aqueous solution is 37%, the mass concentration of the glutaraldehyde aqueous solution is 50%, and the mass concentration of chitosan in the chitosan-acetic acid aqueous solution is 10%.

[0010] In the present invention, the chitosan preferably has a deacetylation degree of 50%-60% and a molecular weight of 1000-2000. Formaldehyde is an amino protective agent of chitosan; glutaraldehyde is a crosslinking agent to prepare crosslinked chitosan, and protonation modification is performed. Generally, the chitosan is crosslinked and protonated, and has a certain adsorption effect on anions in water such as sulfate ions, fluoride ions, nitrate ions, etc.

[0011] More preferably, the heating temperature is 30°C;

[0012] More preferably, the stirring speed is 600 rpm and the stirring time is 40 min;

[0013] More preferably, the reaction time is 90 min;

[0014] More preferably, the continued reaction time is 90 min;

[0015] More preferably, the temperature is raised to 50-60° C. and the curing time is 4-8 hours.

[0016] Preferably, the preparation method of the barium salt-doped nano-CaCO3 microspheres comprises the following steps: uniformly dispersing barium salt nanoparticles in water, adding the resulting solution to a reverse microemulsion system of poly(acrylamide-co-sodium acrylate) microgel, adding calcium chloride after stirring, continuing stirring, then adding ammonium carbonate, stirring again to start a mineralization reaction, and after mineralization, washing, centrifuging, and drying to obtain the barium salt-doped nano-CaCO3 microspheres.

[0017] More preferably, the barium salt nanoparticles are barium chloride or barium nitrate nanoparticles, and the particle size is 20-50 nm.

[0018] Under stirring, the hydrophilic barium salt will enter the poly(acrylamide-co-sodium acrylate) microgel. After adding ammonium carbonate powder, calcium carbonate will grow inside the microgel and eventually wrap the barium salt nanoparticles therein. After mineralization, the sample is taken out and washed with anhydrous ethanol and deionized water to obtain barium salt-doped nano-CaCO3 microspheres.

[0019] More preferably, the mass proportions of the barium salt nanoparticles, water, poly(acrylamide-co-sodium acrylate) microgel, calcium chloride and ammonium carbonate are 10-20 parts, 50-80 parts, 500-600 parts, 80-85 parts and 110-120 parts respectively.

[0020] More preferably, the stirring speed is 250 rpm for 30 min;

[0021] More preferably, the stirring speed is 250 rpm and the stirring time is 3.5 h;

[0022] More preferably, the rotation speed of the stirring again to start the mineralization reaction is 250 rpm and the time is 3-4 hours.

[0023] Preferably, the preparation method of the polyacrylate / barium salt doped nano-CaCO3 composite emulsion comprises the following steps: pouring a mixture of 10-20 parts of barium salt doped CaCO3 microspheres, 0.8-1.2 parts of emulsifier and 120-140 parts of water into a mixture of 20-30 parts of acrylate, 0.3-0.5 parts of ammonium persulfate and 0.5-0.8 parts of emulsifier, stirring evenly and adjusting the pH value to 7-9, adding part of the initiator aqueous solution after heating in a water bath to initiate a polymerization reaction, keeping the temperature after the initial exothermic peak of the polymerization reaction, adding 0.3-0.5 parts of emulsifier and the remaining initiator aqueous solution, and then continuously dripping a monomer mixture prepared by 15-20 parts of acrylate and 20-30 parts of water, continuing to keep the temperature after the dripping is completed, and cooling to obtain the polyacrylate / barium salt doped nano-CaCO3 composite emulsion.

[0024] More preferably, the acrylate is one or two of methyl acrylate, ethyl acrylate, methyl methacrylate, and butyl acrylate.

[0025] The hydrolysis of acrylate is a reversible reaction, but it is more thorough under alkaline conditions. When acrylate is hydrolyzed under alkaline conditions, a tetrahedral intermediate anion is first formed. Therefore, the electron-withdrawing group on the carbon near the carbonyl group can stabilize the tetrahedral anion and promote the reaction; at the same time, the smaller the steric hindrance, the more conducive to the hydrolysis. If there are more substituents on the carbonyl carbon in acrylate, the greater the steric hindrance, the slower the reaction rate. Ethyl acrylate has one more -CH2 on the alkyl carbon connected to oxygen than methyl acrylate, which increases the steric hindrance. Therefore, the number of carboxyl groups released in the same time is less than that of methyl acrylate. Similarly, the amount of carboxyl groups released by butyl acrylate is lower. Since methyl methacrylate has one more -CH3 than methyl acrylate, the former has a greater reaction steric hindrance and a relatively slower hydrolysis rate.

[0026] More preferably, the emulsifier is an anionic emulsifier sodium lauryl sulfate.

[0027] More preferably, the water bath is heated to 70°C;

[0028] More preferably, the insulation time is 60 minutes;

[0029] More preferably, the continued insulation time is 2 hours.

[0030] More preferably, the partial initiator aqueous solution and the remaining initiator aqueous solution are prepared by mixing 0.05-0.1 parts of initiator with 5-10 parts of deionized water, and the initiator is one or both of ammonium persulfate and potassium persulfate.

[0031] The second technical solution provided by the present invention is:

[0032] A method for preparing the above-mentioned internal sulfate corrosion resistance agent comprises the following steps: weighing raw materials according to mass parts, adding anion exchange chitosan to acetic acid solution to prepare anion exchange chitosan solution with a solid content of 20wt%, adding sodium polyacrylate to polyacrylate / barium salt doped nano-CaCO3 composite emulsion, dispersing at a high speed of 1500-3000rpm for 3-5min, adding barium salt doped nano-CaCO3 microspheres, continuing to stir at the same speed for 15-20min, adding the anion exchange chitosan solution, and continuing to stir at the same speed for 15-20min to obtain the internal sulfate corrosion resistance agent.

[0033] Compared with the prior art, the present invention has the following advantages and technical effects:

[0034] The anti-internal sulfate corrosion agent provided by the present invention has excellent resistance to sulfate corrosion inside concrete caused by sulfate carried by quick-setting agents and sand and gravel aggregates, and can improve the durability of concrete. The addition of the anti-internal sulfate corrosion agent provided by the present invention will not reduce the strength of concrete. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0040] The normal temperature of the present invention refers to 25±2°C.

[0041] In the embodiments of the present invention, “parts” refer to “parts by mass” unless otherwise specified.

[0042] The preparation of the poly(acrylamide-co-sodium acrylate) microgel in the embodiment of the present invention is basically carried out according to the method described in the literature "Effect of chemical composition on properties of pH-responsive poly(acrylamide-co-acrylic acid) microgels prepared by inverse microemulsionpolymerization". The specific preparation method is: the sum of the amount of the polymerized olefin monomers acrylic acid and acrylamide is maintained at 24 parts, and a microgel with a molar percentage of sodium acrylate (SA) of 50% is prepared. The preparation process is as follows: 43.6 parts of Span80 and 33.8 parts of Tween80 are added to a three-necked flask containing 420 parts of isooctane in sequence, and the temperature is maintained at 30°C and electromagnetic stirring is performed to obtain an oil phase; 11.92 parts of AM, 12.08 parts of AA, 6.716 parts of NaOH, and 2.4 parts of MBA are dissolved in 93.4 parts of deionized water, and stirred in a beaker to mix them evenly to obtain an aqueous phase, and the aqueous phase is added dropwise to the oil phase, and the original stirring speed is maintained to obtain an inverse microemulsion. After N2 was introduced to remove oxygen for 0.5 h, 0.12 parts of APS and 0.06 parts of NaHSO3 as initiators were added to maintain N2 protection. After the reaction lasted for 4 h, N2 was removed from the system. At this time, the prepared microgel was evenly dispersed in isooctane under the stabilization of the external emulsifier and used as a template for the subsequent mineralization reaction.

[0043] Example 1 A method for preparing an agent for resisting internal sulfate corrosion

[0044] S1. Preparation of anion exchange chitosan: 50 parts of carbon tetrachloride, 50 parts of petroleum ether and 10 parts of Span-80 were placed in a three-necked flask, and 120 parts of chitosan-acetic acid aqueous solution (10 wt.%) were added under electric stirring at 30°C, and stirred at a speed of 600 rpm. After 40 minutes, the chitosan solution was dispersed into beads, and 180 parts of formaldehyde solution (37 wt.%) was added dropwise, and stirred at room temperature at a speed of 600 rpm. After the reaction for 90 minutes, the reaction was continued by adding 8 parts of glutaraldehyde (50wt.%), stirred at 600rpm at room temperature, reacted for 90min, then added with NaOH to adjust the solution pH to 8, heated to 60℃ and reacted for 6h to solidify the beads, filtered, washed with water until neutral, extracted with acetone, filtered, washed, and vacuum dried. The prepared amino-protected glutaraldehyde cross-linked chitosan is anion exchange chitosan. 10 parts of glutaraldehyde cross-linked chitosan are added to 40 parts of 2% acetic acid solution to prepare glutaraldehyde cross-linked chitosan solution;

[0045] S2. Preparation of CaCO3 microspheres doped with barium salts: 10 parts of barium nitrate nanoparticles were added to 60 parts of deionized water for ultrasonic dispersion. After being evenly dispersed, they were added to the reverse microemulsion system of 500 parts of poly(acrylamide-co-sodium acrylate) microgel. Under stirring (250 rpm, 30 min), the hydrophilic barium nitrate entered the microgel. Then 83 parts of calcium chloride powder were added. After stirring (250 rpm, 3.5 h), 117 parts of ammonium carbonate powder were added. Stirring was continued (250 rpm, 3 h) to achieve the growth of calcium carbonate inside the microgel and finally encapsulate the barium nitrate nanoparticles. After washing with anhydrous ethanol and deionized water, the mixture was centrifuged and dried to obtain CaCO3 microspheres doped with barium salts.

[0046] S3. The mixture of 20 parts of barium salt-doped CaCO3 microspheres, 1 part of sodium dodecyl sulfate, and 130 parts of deionized water was poured into a four-necked flask containing 15 parts of methyl methacrylate, 15 parts of methyl acrylate, 0.5 parts of ammonium persulfate, and 0.7 parts of sodium dodecyl sulfate, and the mixture was stirred for 30 minutes, and a sodium hydroxide solution was added dropwise to adjust the pH value to 8. After the water bath was slowly heated to 70 ° C, 0.05 parts of ammonium persulfate and 5 parts of deionized initiator solution were added to initiate polymerization. After the exothermic peak of the initial polymerization reaction, 60 minutes were kept warm, 0.35 parts of sodium dodecyl sulfate and 0.05 parts of ammonium persulfate were added with 10 parts of deionized water to prepare a mixed solution, and 15 parts of methyl methacrylate, 5 parts of methyl acrylate and 30 parts of a monomer mixture prepared with deionized water were continuously added dropwise, and the addition was completed. After keeping warm for 2 hours, the polyacrylate / barium salt-doped nano-CaCO3 composite emulsion was obtained after cooling;

[0047] S4: Add 1.3 parts of sodium polyacrylate to 100 parts of polyacrylate / barium salt-doped nano-CaCO3 composite emulsion and disperse at a high speed of 2000 rpm for 5 minutes, then add 8 parts of barium salt-doped nano-CaCO3 microspheres, continue stirring at the same speed for 20 minutes, add 50 parts of glutaraldehyde cross-linked chitosan solution, and continue stirring at the same speed for 15 minutes to prepare an anti-internal sulfate corrosion agent.

[0048] Example 2 A method for preparing an agent for resisting internal sulfate corrosion

[0049] S1. Preparation of anion exchange chitosan: 60 parts of carbon tetrachloride, 60 parts of petroleum ether and 15 parts of Span-80 were placed in a three-necked flask, and 100 parts of chitosan-acetic acid aqueous solution (10 wt.%) were added under electric stirring at 30°C, and stirred at a speed of 600 rpm. After 40 minutes, the chitosan solution was dispersed into beads, and 160 parts of formaldehyde solution (37 wt.%) was added dropwise, and stirred at a speed of 600 rpm at room temperature. After the reaction for 90 minutes, the reaction was continued by adding 10 parts of glutaraldehyde (50wt.%), stirred at 600rpm at room temperature, reacted for 90min, then added with NaOH to adjust the solution pH to 8, heated to 60℃ and reacted for 6h to solidify the beads, filtered, washed with water until neutral, extracted with acetone, filtered, washed, and vacuum dried. The prepared amino-protected glutaraldehyde cross-linked chitosan is anion exchange chitosan. 8 parts of glutaraldehyde cross-linked chitosan are added to 40 parts of 2% acetic acid solution to prepare glutaraldehyde cross-linked chitosan solution;

[0050] S2. Preparation of barium salt-doped CaCO3 microspheres: Take 20 parts of barium chloride nanoparticles and add them to 80 parts of deionized water for ultrasonic dispersion. After uniform dispersion, add them to the reverse microemulsion system of 600 parts of poly(acrylamide-co-sodium acrylate) microgel. Under stirring (250 rpm, 30 min), the hydrophilic barium chloride nanoparticles will enter the microgel. Then add 83 parts of calcium chloride powder and stir (250 rpm, 3.5 h). Then add 117 parts of ammonium carbonate powder and continue stirring (250 rpm, 4 h) to achieve the growth of calcium carbonate inside the microgel and finally encapsulate the barium chloride nanoparticles. Wash with anhydrous ethanol and deionized water, centrifuge and dry to obtain barium salt-doped CaCO3 microspheres.

[0051] S3 and S4 are the same as in Example 1.

[0052] Example 3 Preparation method of an anti-internal sulfate corrosion agent

[0053] S1-S3 are the same as in Example 1;

[0054] S4. Add 1.5 parts of sodium polyacrylate to 120 parts of polyacrylate / barium salt-doped nano-CaCO3 composite emulsion and disperse at a high speed of 2000rpm for 5 minutes, then add 10 parts of barium salt-doped nano-CaCO3, continue stirring at the same speed for 20 minutes, add 25 parts of glutaraldehyde cross-linked chitosan solution, continue stirring at the same speed for 15 minutes, and prepare an anti-internal sulfate corrosion agent.

[0055] Example 4

[0056] S1 and S2 are the same as in Example 1;

[0057] S3. The mixture of 20 parts of barium salt-doped CaCO3 microspheres, 1.2 parts of sodium dodecyl sulfate, and 130 parts of deionized water was poured into a four-necked bottle containing 15 parts of butyl acrylate, 10 parts of methyl acrylate, 0.5 parts of ammonium persulfate, and 0.8 parts of sodium dodecyl sulfate, and stirred for 30 minutes. A sodium hydroxide solution was added dropwise to adjust the pH value to 8, and the water bath was slowly heated to 70 ° C. After that, 0.05 parts of ammonium persulfate and 5 parts of deionized initiator solution were added to initiate polymerization. After the exothermic peak of the initial polymerization reaction, 60 minutes were kept warm, 0.35 parts of sodium dodecyl sulfate and 0.05 parts of ammonium persulfate were added with 10 parts of deionized water to prepare a mixed solution, and 15 parts of butyl acrylate, 5 parts of methyl acrylate and 30 parts of a monomer mixture prepared with deionized water were continuously added dropwise. After the addition was completed, the mixture was kept warm for 2 hours, and the polyacrylate / barium salt-doped nano-CaCO3 composite emulsion was obtained after cooling;

[0058] S4 is the same as Example 1.

[0059] Example 5 A method for preparing an agent for resisting internal sulfate corrosion

[0060] S1 and S2 are the same as in Example 1;

[0061] S3. Pour 20 parts of barium salt-doped CaCO3 microspheres, 1.2 parts of sodium dodecyl sulfate, and 130 parts of deionized water into a four-necked bottle containing 15 parts of butyl acrylate, 10 parts of methyl acrylate, 0.35 parts of ammonium persulfate, and 0.8 parts of sodium dodecyl sulfate, stir and mix for 30 minutes, add sodium hydroxide solution to adjust the pH value to 8, slowly heat the water bath to 70°C, add 0.05 parts of ammonium persulfate and 5 parts of deionized initiator solution to initiate polymerization, keep warm for 60 minutes after the exothermic peak at the beginning of the polymerization reaction, add 0.35 parts of sodium dodecyl sulfate and 0.05 parts of ammonium persulfate and 10 parts of deionized water to prepare a mixed solution, and continuously add 10 parts of butyl acrylate, 5 parts of methyl acrylate and 30 parts of deionized water to prepare a monomer mixture, keep warm for 2 hours after the addition is complete, and obtain a polyacrylate / barium salt-doped nano-CaCO3 composite emulsion after cooling.

[0062] S4. Add 1.0 part of sodium polyacrylate to 120 parts of polyacrylate / barium salt-doped nano-CaCO3 composite emulsion and disperse at a high speed of 2000rpm for 5 minutes, then add 10 parts of barium salt-doped nano-CaCO3, continue stirring at the same speed for 20 minutes, add 25 parts of glutaraldehyde cross-linked chitosan solution, continue stirring at the same speed for 15 minutes, and prepare an anti-internal sulfate corrosion agent.

[0063] Comparative Example 1

[0064] CN 114656184 А A sulfate-resistant concrete admixture and its preparation method and concrete embodiment 1, wherein the amount of the prepared sulfate-resistant concrete admixture accounts for 12% of cement.

[0065] Comparative Example 2

[0066] CN 110183136 B A concrete anticorrosion and rust inhibitor and its preparation method, embodiment 1, the amount of the prepared concrete anticorrosion and rust inhibitor accounts for 10% of cement.

[0067] Effect verification

[0068] The anti-internal sulfate corrosion agents prepared in Examples 1-5 were all added at 8% of the mass of the adhesive (cement), and the comparative proportion was added to the preparation process of shotcrete according to the recommended dosage, and the corresponding mixing water was deducted. The formula of the shotcrete is shown in Table 1, wherein the accelerator model is GK-3B (purchased from Shijiazhuang Changan Yucai Building Materials Co., Ltd.), and meets Q / CR807-2020 "Liquid alkali-free accelerator for tunnel shotcrete".

[0069] According to the Standard for Test Methods for Mechanical Properties of Ordinary Concrete (GB / T50080-2002), the mechanical properties of the anti-internal sulfate corrosion agent prepared by adding Examples 1-5 and Comparative Examples 1-5 were tested, and the results are shown in Table 2.

[0070] Table 1 Formula of shotcrete

[0071] Cement (kg) Sand (kg) Stone (kg) Water (kg) Water reducing agent for concrete (kg) Accelerator (kg) Dosage 450 890 850 180 4.5 31.5

[0072] Table 2 Mechanical properties of shotcrete

[0073] 24h (Mpa) 7d (Mpa) 28d (Mpa) 180d (Mpa) Example 1 30.9 42.5 57.1 58.6 Example 2 30.1 42.1 56.7 58.5 Example 3 30.8 42.5 57.4 59.2 Example 4 30.6 41.9 56.4 58.2 Example 5 31.2 42.6 57.8 59.6 Comparative Example 1 24.2 39.4 56.9 58.0 Comparative Example 2 26.8 43.7 55.5 56.1 Blank group 1 23.5 39.8 53.2 52.2

[0074] It can be found from Table 2 that after Examples 1-5 are used as an anti-internal sulfate corrosion agent in combination with an accelerator, the 24h strength of the concrete reaches more than 30Mpa, which is significantly better than Comparative Example 1 (the amount added is 12% of the cement) and Comparative Example 2 (the amount added is 10% of the cement), and can improve the early strength of the shotcrete to a certain extent, and also effectively improve the later strength of the concrete.

[0075] The anti-internal sulfate corrosion agent of the embodiment of the present invention is added at 8% of the colloid material, and the mortar is prepared according to the recommended dosage of the comparative proportion. The corresponding mixing water dosage is deducted according to the solid content of the anti-corrosion preservative, and the durability performance of the mortar is tested respectively. The expansion coefficient, corrosion resistance coefficient and chloride ion diffusion coefficient ratio refer to JC / T1011-2021 "Concrete Anti-Corrosion Preservative" as the test standard, and the specific performance test results are shown in Table 3. The expansion rate test method refers to the potential expansion performance test method (P method) of GB / / T749-2009 "Cement Anti-Sulfate Erosion Test Method". The principle of the method is to add a certain amount of dihydrate gypsum to the cement so that the total content of SO3 in the cement reaches a specified amount, so that the excess SO3 directly reacts with the minerals in the cement that affect the sulfate resistance to produce expansion, and then the expansion rate of the mortar specimen at a specified age is measured to measure the potential sulfate resistance of the cement mortar. The specific performance test results are shown in Table 4.

[0076] Table 3 Concrete resistance to harmful ion corrosion performance

[0077] Corrosion resistance factor Chloride ion diffusion coefficient ratio / % Expansion coefficient Example 1 1.22 0.41 0.94 Example 2 1.25 0.38 0.92 Example 3 1.29 0.41 0.89 Example 4 1.23 0.44 0.94 Example 5 1.31 0.38 0.91 Comparative Example 1 1.21 0.55 1.08 Comparative Example 2 1.12 0.67 1.15 Standard requirements ≥0.9 ≤0.85 ≤1.5

[0078] Table 4 Expansion rate of mortar after simultaneous 180d erosion by internal and external sulfates

[0079] 180d tap water curing expansion rate <![CDATA[Swelling rate after soaking in 180d5% N2SO4 solution]]> Example 1 0.08% 0.09% Example 2 0.08% 0.09% Example 3 0.07% 0.08% Example 4 0.08% 0.09% Example 5 0.07% 0.08% Comparative Example 1 0.12% 0.14% Comparative Example 2 0.15% 0.16% Blank group (containing the same proportion of gypsum, without anti-corrosion preservatives) 0.18% 0.23%

[0080] The following conclusions can be drawn from the experimental data in Table 3 and Table 4: The anti-internal sulfate corrosion agent provided by the present invention is applied to cement-based materials, and a good resistance effect can be achieved under both internal sulfate and external sulfate corrosion modes, which is manifested in a higher corrosion resistance coefficient, a lower chloride ion diffusion coefficient ratio and a lower expansion rate, and has no negative impact on the early and late strength of concrete.

[0081] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. An anti-internal sulfate corrosion agent, characterized in that: The raw materials include the following in parts by weight: 5-10 parts of anion exchange chitosan, 8-10 parts of barium salt doped nano-CaCO3 microspheres, 100-120 parts of polyacrylate / barium salt doped nano-CaCO3 composite emulsion and 1-1.5 parts of sodium polyacrylate.

2. The anti-internal sulfate corrosion agent according to claim 1, characterized in that: The preparation method of the anion exchange chitosan comprises the following steps: heating an organic solvent mixture, adding chitosan-acetic acid aqueous solution under stirring, continuing stirring to disperse the chitosan-acetic acid aqueous solution into beads, then dripping formaldehyde solution, dripping glutaraldehyde after reaction, continuing reaction, adjusting pH to 7.5-8.5, heating reaction to solidify the beads, filtering, washing with water to neutrality, extracting, filtering, washing, vacuum drying, and preparing amino-protected glutaraldehyde cross-linked chitosan, namely the anion exchange chitosan.

3. The anti-internal sulfate corrosion agent according to claim 2, characterized in that: The organic solvent mixture comprises, by weight, 50-60 parts of carbon tetrachloride, 50-60 parts of petroleum ether and 10-15 parts of Span-80; and / or The mass proportions of the chitosan-acetic acid aqueous solution, the formaldehyde solution and the glutaraldehyde solution are 100-120 parts, 160-180 parts and 8-10 parts respectively, and the mass concentration of chitosan in the chitosan-acetic acid aqueous solution is 10%.

4. The anti-internal sulfate corrosion agent according to claim 2, characterized in that: The heating temperature is 30°C; and / or The stirring is continued at a speed of 600 rpm for 40 min; and / or The reaction time is 90 min; and / or The continued reaction time is 90 min; and / or The temperature is raised to 50-60° C. and the curing time is 4-8 hours.

5. The anti-internal sulfate corrosion agent according to claim 1, characterized in that: The preparation method of the barium salt doped nano-CaCO3 microspheres comprises the following steps: uniformly dispersing barium salt nanoparticles in water, adding the obtained solution into a reverse microemulsion system of poly(acrylamide-co-sodium acrylate) microgel, adding calcium chloride after stirring, continuing stirring, then adding ammonium carbonate, stirring again to start a mineralization reaction, and after mineralization, washing, centrifuging, and drying to obtain the barium salt doped nano-CaCO3 microspheres.

6. The anti-internal sulfate corrosion agent according to claim 5, characterized in that: In terms of mass, the barium salt nanoparticles, water, poly(acrylamide-co-sodium acrylate) microgel, calcium chloride and ammonium carbonate are 10-20 parts, 50-80 parts, 500-600 parts, 80-85 parts and 110-120 parts respectively.

7. The anti-internal sulfate corrosion agent according to claim 5, characterized in that: The stirring speed is 250 rpm for 30 min; and / or The stirring is continued at a speed of 250 rpm for 3.5 hours; and / or The rotation speed of the stirring again to start the mineralization reaction is 250 rpm, and the time is 3-4 hours.

8. The anti-internal sulfate corrosion agent according to claim 1, characterized in that: The preparation method of the polyacrylate / barium salt doped nano-CaCO3 composite emulsion comprises the following steps: pouring a mixture of 10-20 parts of barium salt doped CaCO3 microspheres, 0.8-1.2 parts of emulsifier and 120-140 parts of water into a mixture of 20-30 parts of acrylate, 0.3-0.5 parts of ammonium persulfate and 0.5-0.8 parts of emulsifier, stirring evenly and adjusting the pH value to 7-9, adding part of the initiator aqueous solution after heating in a water bath to initiate a polymerization reaction, keeping the temperature after the initial exothermic peak of the polymerization reaction, adding 0.3-0.5 parts of emulsifier and the remaining initiator aqueous solution, and then continuously dripping a monomer mixture prepared by 15-20 parts of acrylate and 20-30 parts of water, continuing to keep the temperature after the dripping is completed, and cooling to obtain the polyacrylate / barium salt doped nano-CaCO3 composite emulsion.

9. The anti-internal sulfate corrosion agent according to claim 8, characterized in that: The water bath is heated to 70°C; and / or The insulation time is 60 min; and / or The time of continuing to keep warm is 2h.

10. A method for preparing the anti-internal sulfate corrosion agent according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: weighing raw materials according to mass parts, adding anion exchange chitosan into acetic acid solution to prepare anion exchange chitosan solution with a solid content of 20wt%, adding sodium polyacrylate into polyacrylate / barium salt doped nano-CaCO3 composite emulsion, dispersing at a high speed of 1500-3000rpm for 3-5min, adding barium salt doped nano-CaCO3 microspheres, continuing stirring at the same speed for 15-20min, adding the anion exchange chitosan solution, continuing stirring at the same speed for 15-20min, and obtaining the anti-internal sulfate corrosion agent.

Citation Information

Patent Citations

  • A concrete corrosion inhibitor and rust retardant and its preparation method

    CN110183136B

  • Preparation method of O-carboxymethyl chitosan resin

    CN104045842A

  • Preparation method of protective coating material for marine surrounding buildings

    CN111995307A